Risk factors and prognostic influence of infection in a single cohort of 87 adults with systemic lupus erythematosus: This work was presented in part at the 38th Interscience Conference on Antimicrobial Agents and Chemotherapy, San Diego, California, USA, 1998 (abstract L-61), and at the Meeting of the American College of Rheumatology, Boston, Massachusetts, November 1999 (abstract 174). Issue 12 (1st December 2001) - Noël, V; Lortholary, O; Casassus, P; Cohen, P; Généreau, T; André, M-H; Mouthon, L; Guillevin, L
Abstract : OBJECTIVES: To describe infectious complications and analyse their risk factors and prognostic role in adults with systemic lupus erythematosus (SLE). METHODS: A monocentric cohort of 87 adults with SLE (1960–1997) was studied to determine the risk factors for infection (disease activity evaluated by SLAM and SLEDAI scores, type of organ(s) involved or any biological abnormality, specific treatments) by comparing patients who had suffered at least one infectious episode (n=35; 40%) with non-infected patients (n=52; 60%). Prognostic indicators were assessed by comparing survivors at 10 years with non-survivors. RESULTS: Of the 57 infectious episodes, 47 (82%) were of bacterial origin, 16 (28%) were pneumonia, and 46 (81%) were community acquired. According to univariate analysis, significant risk factors for infection were: severe flares, lupus glomerulonephritis, oral or intravenous corticosteroids, pulse cyclophosphamide, and/or plasmapheresis. No predictors were identified at the time of SLE diagnosis. Multivariate analyses retained intravenous corticosteroids (p<0.001) and/or immunosuppressants (p<0.01) as independent risk factors for infection, which was the only factor for death after 10 years of evolution (p<0.001). CONCLUSION: In adults with SLE, infections are common and most often caused by community acquired bacteria. Intravenous corticosteroids and immunosuppressants are independent risk factors for infection, which is the only independent risk factor for death after 10 years of SLE evolution.